Upaya Pencegahan Kecemasan dan Shivering Pada Pasien Pasca Anestesi Melalui Dukungan Keluarga Yang Optimal - Naufal Annasy; Mustikasari Mustikasari (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2022)
This study aims to analyze the effectiveness of family support in preventing anxiety and shivering in post-anesthesia patients. Anxiety and shivering are common complications after anesthesia that can negatively impact the patient’s recovery process. Both of these issues can lead to prolonged hospital stays, increased medical costs, and reduced patient satisfaction. Family support plays a crucial role in providing psychological and physiological comfort, which may reduce anxiety levels and the incidence of shivering, thus aiding the recovery process. This research uses a quantitative approach with a quasi-experimental design, comparing the outcomes of patients who receive family support to those who do not. The sample consists of 60 post-anesthesia patients, who are divided into two groups: an intervention group that receives family support and a control group that does not. The data collected includes anxiety levels and the frequency of shivering, measured using standardized scales. The results show that patients in the intervention group, who received active family support, have significantly lower anxiety levels (p < 0.05) and experience fewer episodes of shivering compared to the control group. These findings suggest that family support plays a crucial role in improving the recovery of post-anesthesia patients by addressing both emotional and physical challenges. The study emphasizes the importance of including family members in the recovery process and recommends that healthcare providers integrate family support strategies into post-anesthesia care plans to enhance patient recovery outcomes.